Programas sociais de combate à pobreza na América Latina: uma análise comparativa entre o Programa de Educação, Saúde e Alimentação e o Programa Fome Zero - Borges, Michelle da Silva (2007)
The poverty has been a constant in the Latin America society. Its persistence and resistance to the conventional social policies, they bring it again in the decade of 1990 to the academic debate and the several governments' public calendar in Latin America. What is evident, in several studies accomplished in this period, it is that the poverty in this area possesses a historical-structural character, and that, therefore, the means to face it request actions that break up with its vicious circle and not it minimizes only its effects. That, in the last decade it has been enlarging in America Latin combat actions to the poverty. This dissertation she intended to analyze two of this social programs of combat to the poverty, had as innovators in Latin America, the ZERO HUNGER PROGRAM in Brazil and the PROGRESA PROGRAM, today, OPORTUNITIES in Mexico. The central objective went compare the conceptions theoretical originals of these programs and to try to answer, inside of the context of a new orientation of the social policy in Latin America, there is been or non differences among him. We reached the conclusion that there are differences and that, these they are bounded to the following points: i) different perception of combat of the poverty; ii) focusing versus universal and, iii) it focus territorial. In a general way we observed that, the Brazilian project, by means of a proposal of food security, looks for to rescue the debate of the universal of the social rights, that is not a little in a context in which the " new " model of politics social focusing prevails. With relationship to the Mexican program, by means of the analysis of its project, we observed that its diagnosis and its proposals join with the calendar of reforms social defended for the prescription neoliberal.